An Experimental Determination of Coupled Thermal and Moisture Expansion of Plasters - Å Ãn, Peter; Pavlendová, Gabriela; LukoviÄovÃ¡, Jozefa; Kubliha, Marián (International Journal of Advanced Research in Engineering; Vol 1 No 3 (2015): International Journal of Advanced Research in Engineering, 2015)
The objective of this paper is to evaluate, together with adsorption and desorption processes, moisture and temperature induced deformations of two plasters. The measurements are performed for moisture content from the dry state to the saturation water content and temperature range of 5 â€“ 60Â°C. The coupled temperature and moisture induced length differences are measured using LVDT MACRO SENSOR SBP 375040.